2015
DOI: 10.1007/s40653-015-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Focused Cognitive Behavioral Therapy for Commercially Sexually Exploited Youth

Abstract: Commercially sexually exploited children and adolescents (“commercially exploited youth”)present numerous clinical challenges that have led some mental health providers to question whether current evidence-based treatments are adequate to address the needs of this population. This paper 1) addresses commonalities between the trauma experiences, responses and treatment challenges of commercially exploited youth and those of youth with complex trauma; 2) highlights the importance of careful assessment to guide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Second, the girls’ concerns about the quality of mental health services align with provider concerns about the best practices for treating CSE youth (Cohen, Mannarino, & Kinnish, 2017). CSE youth represent a population with a high prevalence of complex trauma, disrupted attachments and loss, substance use, risky behaviors, and poor social determinants of health—including homelessness, poverty, and decreased social supports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the girls’ concerns about the quality of mental health services align with provider concerns about the best practices for treating CSE youth (Cohen, Mannarino, & Kinnish, 2017). CSE youth represent a population with a high prevalence of complex trauma, disrupted attachments and loss, substance use, risky behaviors, and poor social determinants of health—including homelessness, poverty, and decreased social supports.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that CSE youth experience high rates of childhood emotional, physical, and sexual abuse (Stoltz et al, 2007); one study found the majority of traumatic exposures occurred in the caregiving environment (Cole, Sprang, Lee, & Cohen, 2014). Given the complex trauma in this population—which can be tied to difficulty trusting providers and engaging in treatment, along with demonstrating risky behaviors—clinicians and experts have questioned if current therapy approaches appropriately meet the needs of CSE youth (Cohen et al, 2017). There is a general dearth of research studies on treatment for CSE youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linda also displayed a common symptom presentation found in youth who are victims of CSE and suffered complex trauma, namely, externalizing behavior problems and associated risky behaviors (e.g., running away, substance abuse, truancy; Cohen et al, 2017). Two of her measures (YSR and CBCL) indicated high levels of externalizing behaviors, which would include truancy, substance abuse, and so forth.…”
Section: Case Conceptualizationmentioning
confidence: 99%
“…Although the treatment needs of victims of CSE is strong, few victims are referred for treatment (Goździak & MacDonnell, 2007). Given the prevalence of CSE, Cohen, Mannarino, and Kinnish (2017) state there is a need “for effective interventions to meet victim needs, as well as improved collaboration, coordination and communication across the multiple systems that serve them” (p. 1).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%